1980
DOI: 10.1111/j.1365-2621.1980.tb00965.x
|View full text |Cite
|
Sign up to set email alerts
|

Proximate analysis of five varieties of winged beans, Psophocarpus tetragonolobus (L.) DC*

Abstract: The proximate composition was determined for the mature seeds of five varieties of winged beans, Psophocarpus tetragonolobus (L.) DC. The results showed that the varieties analyzed had a high protein and fat content, which was similar to soybeans. The protein content (mean * standard deviation) of the five varieties as received was 36.0 * 1.8%, the fat content, 15.2 & 1.2% and the moisture content 10.4 -+ 1.5%. The endosperm in winged bean variety TPT-2 was found to constitute 84% of the dry weight of the seed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 4 publications
(1 reference statement)
2
10
0
Order By: Relevance
“…The ash value of UWBS was 3.52 % which is similar with DWBS (3.42 %). These findings were in agreement by previous research on Pigeon pea (Cajanus cajan L.) with the ash value within the range of 3.3 to 4.9 % (Ghadge et al 2010;Garcia and Palmer 1980). On the other hand, fiber (11.47 %) and carbohydrate (28.87 %) contents of UWBS were nearly similar with DWBS, showing values of 10.35 % and 27.56 %, respectively.…”
Section: Resultssupporting
confidence: 81%
“…The ash value of UWBS was 3.52 % which is similar with DWBS (3.42 %). These findings were in agreement by previous research on Pigeon pea (Cajanus cajan L.) with the ash value within the range of 3.3 to 4.9 % (Ghadge et al 2010;Garcia and Palmer 1980). On the other hand, fiber (11.47 %) and carbohydrate (28.87 %) contents of UWBS were nearly similar with DWBS, showing values of 10.35 % and 27.56 %, respectively.…”
Section: Resultssupporting
confidence: 81%
“…Mature winged bean seeds (see supplementary materials; figures S.1) contain on average around 15-18% fat and 30-37% crude protein, and a favourable amino acid and micronutrient composition (Černý et al 1971;Claydon 1975;Gillespie and Blagrove 1978;Garcia and Palmer 1980;Hildebrand et al 1981b;Gross 1983;Kadam et al 1984). Protein content and fatty acid profiles compare favourably with soybean and chickpea (Cicer arietinum) (Claydon 1975;Kadam et al 1984), and peanut (Garcia et al 1979;Ekpenyong and Borchers 1980a;Garcia and Palmer 1980).…”
Section: Mature Seeds Consumptionmentioning
confidence: 99%
“…Mature winged bean seeds (see supplementary materials; figures S.1) contain on average around 15-18% fat and 30-37% crude protein, and a favourable amino acid and micronutrient composition (Černý et al 1971;Claydon 1975;Gillespie and Blagrove 1978;Garcia and Palmer 1980;Hildebrand et al 1981b;Gross 1983;Kadam et al 1984). Protein content and fatty acid profiles compare favourably with soybean and chickpea (Cicer arietinum) (Claydon 1975;Kadam et al 1984), and peanut (Garcia et al 1979;Ekpenyong and Borchers 1980a;Garcia and Palmer 1980). A comprehensive assessment of the nutritional properties of winged bean seeds and the other edible parts, along with comparisons with other leguminous crops, have being adequately reviewed elsewhere (see for example Claydon 1975Claydon , 1983Kailasapathy and Sandrasegaram 1983;Kadam et al 1984;Kantha and Erdman 1984;Kailasapathy and Macneil 1985;Prakash et al 1991;Lepcha et al 2017).…”
Section: Mature Seeds Consumptionmentioning
confidence: 99%
“…Winged been is not so common in West Bengal vegetables field but it is a very promising crop. Its leaves, flowers, pods, green seeds, dried seeds and tuberous roots are all edible and nutritious (Garcia and Palmar 1980). This plant is listed as one of the under-exploited legumes.…”
Section: Introductionmentioning
confidence: 99%
“…The flower can be eaten raw, fried or steamed, roasted tuber are also edible (Singh et al, 2013). Tuber of winged bean consist of very high amount of protein (8-20%) as compared to the common cultivars of most root crops, flowers of winged bean also contain protein (Garcia and Palmar 1980;Singh et al, 2013). Amoo et al (2006) has reported that crude protein content of winged bean was higher than the cowpeas seeds, pigeon pea, and lime bean.…”
Section: Introductionmentioning
confidence: 99%